2020
DOI: 10.1007/s10531-020-02088-1
|View full text |Cite
|
Sign up to set email alerts
|

How to build a biodiverse city: environmental determinants of bird diversity within and among 1581 cities

Abstract: Cities are novel environments compared with the evolutionary history of the species that reside within them. Collectively, cities and their fauna can be thought of as ecosystems, recognized as playing a critical role in supporting global biodiversity, but they are fundamentally a combination of old species surviving or thriving in a new environment, and the mechanisms and underlying processes which support biodiversity within cities have not been investigated at broad macroecological scales. We aimed to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 132 publications
2
12
1
Order By: Relevance
“…Relative to housing cover, landscape-scale canopy tree cover did not have a strong influence on the richness of native, terrestrial or forest birds across the urbanization gradient sampled. This contrasts with other studies in urban environments which have reported a positive relationship between avian species richness and canopy tree cover, either for landscape units (Chamberlain et al 2019;Callaghan et al 2020) or sites with surrounding tree cover (Callaghan et al 2018;Lerman et al 2021). The lack of a relationship between landscape-scale tree cover and bird richness here may be due to several factors.…”
Section: Landscape Change Across An Urbanization Gradientcontrasting
confidence: 99%
“…Relative to housing cover, landscape-scale canopy tree cover did not have a strong influence on the richness of native, terrestrial or forest birds across the urbanization gradient sampled. This contrasts with other studies in urban environments which have reported a positive relationship between avian species richness and canopy tree cover, either for landscape units (Chamberlain et al 2019;Callaghan et al 2020) or sites with surrounding tree cover (Callaghan et al 2018;Lerman et al 2021). The lack of a relationship between landscape-scale tree cover and bird richness here may be due to several factors.…”
Section: Landscape Change Across An Urbanization Gradientcontrasting
confidence: 99%
“…This last index is negatively related to the distance from the cerrado and positively related to the diversity of environments and the number of patches present in the landscape, suggesting an increasing diversity of species. This situation is already observed in other regions (Callaghan et al, 2021;de Groot et al, 2021;Garizábal-Carmona & Mancera-Rodríguez, 2021). Consequently, these results suggest that areas composed of native vegetation, or areas that present the mosaic mentioned above, could have higher species richness than the intensely urbanized areas as shown by Machado et al (2017).…”
Section: Response Of Acoustic Indices To the Urban Gradientsupporting
confidence: 73%
“…Tomasevic and Marzluff (2017) showed that in the most heavily urbanized areas, classed as those with below 12% forest cover on a 1 km 2 scale, secondary hole-nesters nested primarily in places of anthropogenic origin, using nest boxes or platforms (59% of broods). Thus, when designing buildings, modern architects should account for the habitat needs of hole-nesting species, and urban planners should preserve old trees with holes or, alternatively, introduce nest boxes to the environment to support the occurrence of endangered hole nesting birds (Jokimäki et al 2018;Callaghan et al 2021). Rosin et al (2020) suggested that urban designers and architects should draw inspiration from traditional architecture and include different types of nest boxes in their plans.…”
Section: Discussionmentioning
confidence: 99%